2007
DOI: 10.1038/sj.emboj.7601771
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the APPL1 BAR-PH domain and characterization of its interaction with Rab5

Abstract: APPL1 is an effector of the small GTPase Rab5. Together, they mediate a signal transduction pathway initiated by ligand binding to cell surface receptors. Interaction with Rab5 is confined to the amino (N)-terminal region of APPL1. We report the crystal structures of human APPL1 N-terminal BAR-PH domain motif. The BAR and PH domains, together with a novel linker helix, form an integrated, crescent-shaped, symmetrical dimer. This BAR–PH interaction is likely conserved in the class of BAR-PH containing proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
164
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(169 citation statements)
references
References 31 publications
4
164
1
Order By: Relevance
“…Recently, APPL1 was identified as a downstream adaptor of AdipoR1 [6]. Interestingly, APPL1 was previously found to be an effector of Rab5 [38,39]. Furthermore, it has been reported that adiponectin stimulates the interaction between APPL1 and Rab5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, APPL1 was identified as a downstream adaptor of AdipoR1 [6]. Interestingly, APPL1 was previously found to be an effector of Rab5 [38,39]. Furthermore, it has been reported that adiponectin stimulates the interaction between APPL1 and Rab5.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PH domains have been found to bind to protein and DNA (4 -12). In addition, some PH domains have been found to be structurally and functionally integrated with adjacent domains (13,14). A small fraction of PH domain-containing proteins (about 9% of the human proteins) have multiple PH domains arranged in tandem, which have been proposed to function as adaptors but have only been examined in one protein (15,16).…”
mentioning
confidence: 99%
“…The interaction is thought to regulate membrane association of arfaptin. Second, APPL1 is a membrane-trafficking protein that like ASAP1, has a tandem of a BAR and PH domains (Zhu et al, 2007). The two domains fold together to form a binding site for Rab5, which is critical for APPL1 function in endocytosis.…”
mentioning
confidence: 99%